Industrial training report: H Elite Design Hotel Kota Bharu / Nurdiana Syazwani Norhadi - Norhadi, Nurdiana Syazwani (Universiti Teknologi MARA, Perlis, 2023)
This report elaborates about my experiences, activities, and events that I was involved during my internship as an HR intern at H Elite Design Hotel Kota Bharu, Kelantan for six months. This hotel is solely concerned with the provision of guest accommodation and related services like cafes, nightlife, and a number of travel and tourism services. I have started my internship on 28 August 2022 and will be finished on 09 February 2023 which is equal to 24 weeks. Overall, it is such an amazing experience doing an internship here as they give me the opportunity for me to engage and improve my skills so that they can be used for my future career. This report is divided into nine major parts. The initial section of the report is the preliminary pages which overview the executive summary, table of content, and acknowledgement. Following section of the assessment highlights the student profile in a resume figure. The third section of the report focuses on the company profile which talks about the company background, company social site, company philosophies, and organizational chart. The fourth section involves the training’s reflection which talk about working days and times, roles and responsibilities, and intrinsic rewards versus extrinsic rewards. The fifth section of the report is the SWOT analysis which overview the strengths, weaknesses, opportunities, and threats of the company. Next section of the assessment highlights the pros and cons of the weaknesses and need to provide the best solution for it. The seventh section involves the conclusion of the overall report. The eighth section is about the references. Last but not least, the appendices.